MUSE : platform for mobile computer supported collaborative learning - Byrne, Peter (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2011)
Traditionally much research on computer supported collaborative learning, CSCL, focused on either learning through distant collaboration or face-to-face collaboration sharing a computer. A new and emergent area within CSCL is mobile learning. From a pedagogical perspective, classifications of mobile-CSCL (MCSCL) argue that leveraging off affordances of mobile devices allows the development of learning activities that significantly differ from desktop-based CSCL applications. In parallel there is emerging agreement in the mobile learning community that applications informed by the principles of constructionism, contextualisation, and collaboration are of particular value for exploiting the ready-at-hand nature of such devices. In the area of collaboration and creativity, there is agreement that digital video production supports collaborative learning, encourages creativity, self-expression and deeper thinking, and draws on students’ out-of-school interest. However, to date little use has been made of ICT to support the collaborative, as distinct from the video production aspect, of the process. The mobile digital narrative approach, mobileDNA, is a pedagogical methodology to scaffold digital narrative activities and support collaboration with ICT.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin